2010
DOI: 10.2190/cs.12.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Traditional-Age Students Becoming At-Risk: Does Working Threaten College Students' Academic Success?

Abstract: Using survey information from undergraduate students who work while attending two urban commuter institutions in Indiana, this study explores evidence that on average undergraduates under 21 years of age worked more than 31 hours a week while also enrolled in a full course load. The findings in this study indicate that grade point average and possibly course completion were influenced by working more hours per week.While much research in higher education has been devoted to considering at-risk students, high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Students with GPAs in the B-range were less likely to persist compared to students with lower or higher grade point averages. Torres et al (2010) did not find a statistically significant relationship between GPA and persistence.…”
Section: Gpamentioning
confidence: 63%
See 1 more Smart Citation
“…Students with GPAs in the B-range were less likely to persist compared to students with lower or higher grade point averages. Torres et al (2010) did not find a statistically significant relationship between GPA and persistence.…”
Section: Gpamentioning
confidence: 63%
“…John, Paulsen, & Carter, 2005;Torres, Gross, & Dadashova, 2010), dropping out (Ishitani & DesJardins, 2002;Joo et al, 2008), degree completion (Dwyer, McCloud, & Hodson, 2012;Perna, 1998), and time-to-degree (Lam, 1999). Previous research has focused on the effects that family income and financial aid have on college persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increased prevalence of students working alongside their studies raises concerns about its impact on their academic achievement since a large body of research suggests that paid work alongside studies negatively affects academic achievement by reducing the amount of time available for studies (Svanum and Bigatti 2006;Auers et al 2007;Callender 2008;Miller et al 2008;Torres et al 2010;Richardson et al 2014;Logan et al 2016;Mercer et al 2016;Burston 2017;Sanchez-Gelabert et al 2017). Moreover, research suggests that working alongside studies negatively affects the quality of the student's educational experience (Lederer et al 2015;Lowe and Gayle 2016), stress levels and mental health (Miller et al 2008), increases the time to degree (Tur-Sinai et al 2017) and the likelihood of dropping out (Bozick 2007;Torres et al 2010;Moulin et al 2013;Hovdhaugen 2015).…”
Section: Higher Education Expansion and Working Alongside Studiesmentioning
confidence: 99%
“…Balancing work and school is important, because an excessive work schedule while attending school has been shown to have a harmful effect on students through additional stress, diversion from school efforts/activities, and a disconnection with members of the school community (Carney, McNeish, & McColl, 2005;Furr & Elling, 2000;King & Bannon, 2002;Kulm & Cramer, 2006;Torres, Gross, & Dadashova, 2010). Other research has demonstrated that part-time employment while attending college may have a beneficial influence on students by supporting the development of life management skills and easing transitions into their careers (D. X.…”
Section: Literature Reviewmentioning
confidence: 99%